ANALYSIS OF WORK ENVIRONMENT, STANDARD OPERATING PROCEDURES AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE MODERATED BY DEMOCRATIC LEADERSHIP - Hidayatur Rahman; Vivin Maharani Ekowati (Journal of Economic, Bussines and Accounting (COSTING), 2025)
In the era of globalisation and digitalisation, organisations are faced with the demands to improve efficiency, productivity, and service quality continuously. One way to maintain a business is to create and implement a standard to regulate the implementation of company activities. With the existence of a standard, all activities can be carried out in accordance with objectives that align with the company's goals. The objectives of the study are to test and analyze the influence of the work environment on employee performance; the influence of Standard Operating Procedures (SOP) on employee performance; the influence of work discipline on employee performance; to test and analyze the role of leadership style in moderating the influence of the work environment on employee performance; to test and analyze the role of leadership style in moderating the influence of SOP on employee performance and to test and analyze the role of leadership style in moderating the influence of work discipline on employee performance. The study population was 100 employees of PT SGN PG GEMPOLKREP, East Java, from the installation division. Includes: 35 people from the electrical installation division, 35 people from the besali installation division, and 30 people from the milling installation division. The sampling technique used was saturated sampling. Research data were collected through questionnaires and analysed using SmartPLS Version 4. The results showed that the work environment, SOPs, and work discipline significantly influenced employee performance. Meanwhile, the moderation test showed that leadership style was unable to moderate the influence of the work environment, SOPs, and work discipline on employee performance.